친환경 건축 자재로서의 목재: LCI DB 구축의 중요성 - 전진우(Jin-U Jeon); 이정훈(Jeonghun Lee) (KIEAE Journal, 2024)
Purpose: With the intensification of climate change, global initiatives to reduce carbon emissions are gaining momentum. A key approach to mitigating carbon emissions is the sustainable utilization of wood, particularly through its application in the construction sector. Life Cycle Assessment (LCA) is indispensable for quantifying the environmental benefits of timber-structured buildings. To conduct such evaluations effectively, comprehensive databases on construction materials are essential; however, South Korea lacks sufficient research on wood products to support these evaluations. Method: International databases, such as Ecoinvent and Environmental Product Declarations (EPD), were examined, along with South Korean resources, including domestic Environmental Product Declarations and reports from the Korea Forest Service, to analyze differences and identify research needs. Result: The comparative analysis highlights that international LCI databases are extensively developed, providing detailed step-by-step data on wood product manufacturing processes, with a diverse range of wood products registered in the EPD system. In contrast, South Korean databases are limited to individual products, with fewer registered items, underscoring a critical gap. The lack of a comprehensive LCI database impedes thorough environmental evaluations. Consequently, future research should focus on establishing and regularly updating an LCI database for construction wood products to enable rigorous quantitative assessments and comparisons of the environmental benefits associated with sustainable wood use. KCI Citation Count: 0